Evaluating the Internet as a research tool: a comparison of telephone and World Wide Web national park surveys - Gaede, Diane B., author; Vaske, Jerry, advisor; Aukerman, Robert, advisor; Donnelly, Maureen, committee member; Haas, Glenn E., committee member; Crews, Donald L., committee member (Colorado State University. Libraries, 1999)
Use of the World Wide Web for survey data collection is relatively new, along with other forms of electronic surveys such as e-mail. Internet electronic surveys are gaining in use and acceptance as more and more businesses and households acquire personal computers and connect to the Internet. Although web-based surveys offer several advantages (e.g., reduced data collection costs, interactive features encouraging response, use of open-ended items) compared to traditional mail, in-person, and telephone interviews, several methodological questions remain unanswered. For example, to what extent do the findings from a web survey approximate those from a phone survey? Are the demographic characteristics of web respondents statistically similar to a random sample of phone survey respondents? Does topic saliency affect web and telephone data collection? To address these questions, this dissertation compares the findings from two surveys (two versions of a web survey and a telephone survey) containing identical questionnaire items. Both surveys were conducted in collaboration with the National Parks and Conservation Association (NPCA). The dissertation also compares item nonresponse among the two versions of web surveys that were posted. Results show that web respondents resemble the profile user of the Internet; they are younger, male, and more educated than the telephone respondents. Web respondents are also more pro-national park oriented than telephone respondents. Implications for future research and use of electronic surveys are discussed.
Keywords: recreation